FREE STEROLS FROM THE MARINE SPONGE Mycale laevis - VALLE Z., Hernán A.; SANTAFÉ P., Gilmar G. (Vitae, 2009)
The development of marine bioprospection research requires to fortify of marine organisms inventories, which also implies their exhaustive taxonomic classification. From the morphological point of view, the classification of marine sponges is a complex procedure and it is facilitated with the use of chemotaxonomic information based on the composition of its sterols. This study describes the free sterols composition of the Mycale laevis sponge, collected in the Cispatá Bay (Córdoba, Colombia). The subextract of dichloromethane is obtained from the methanol extract of the sponge; this subextract is fractionated through chromatography in column on silica gel, using hexane-ethyl acetate mixtures with a gradual increase of the polarity as a mobile phase. The obtention of the majoritary fraction (Rf = 0.77, silica gel /hexane: ethyl acetate 1:1) and its analysis by means of gas chromatography coupled to mass spectrometry (GC-MS), allows the identification of 9 monohydroxylated sterols with nuclei steroidal Δ0, Δ5 and Δ7 sterols. Stanols (nucleus Δ0) are the most abundant in the sterolic fraction with 71.7% of the total of the present compounds. These results contribute to chemotaxonomics studies marine sponges in the Mycalidae family.